The semantics of (fii) in taizzi dialect: A cultural variation perspective - Turki Mahyoub Qaid Mohammed; Imran Ho-Abdullah; Tan Kim Hua (Penerbit UKM, 2012)
In this paper, we adopt the framework of Cognitive Grammar developed by Langacker (1987) to provide a unified account of the different senses of the Arabic preposition (fii) as used in the Taizzi dialect, one of the dialects spoken in Yemen. The use of (fii) in the Taizzi dialect differs from its use in other dialects of Arabic or even Standard Arabic. That is, (fii) is cognitively characterized differently in the Taizzi dialect from (fii) in other Arabic dialects or (fii) in Standard Arabic. It remains a fact that despite the number of studies that dealt with prepositions, in general; prepositions received little attention and semantic analyses of prepositions remain inadequate (Cienki, 1989; Hamdi, 2002; Lunt, 1982). With regard to prepositions of Arabic, the main problem with the previous studies that dealt with them, in general, is that they examined them from a grammatical point of view focusing on their functions rather than their meanings. Moreover, these studies dealt with prepositions as used in Standard Arabic and were basically established upon the views of old Arab grammarians. The data presented and analyzed in this paper show that speakers of the Taizzi dialect developed the use of (fii) and extended its semantics to cover cognitive domains different from its use in Standard Arabic or other dialects of Arabic. However, what proves to be true about the use of (fii) in the Taizzi dialect need not necessarily be so about other dialects of Arabic. This reflects the cultural variance of prepositional usage in the Taizzi dialect in particular and other dialects of Arabic in general. The paper demonstrates that though speakers of the Taizzi dialect use (fii) in cognitive domains different from its use in Standard Arabic they still cognitively characterize the relation holding between the Trajector (TR) and the Landmark (LM) as a containment relation.